Karakterisasi Korosi Baja SS-430 pada lingkungan NaCL - Heri Jodi (Pusbindiklat - LIPI, 2010)
SS-430 is a ferrite type alloy that can be selected for the base material of sea-water duct-pipes in the water supply system of a power reactor, but in general the ferritic alloy is not as good as austenitic with respect to corrosion resistance. Then NaCl environment is used to examine corrosion rate of SS-430. The corrosion was observed in four concentrations of NaCl solution. The experiments were carried out using M-273 EG&G potentiostate test instrument with polarization methode. The microstructure of post-corrosion samples were analyzed with an EDS attached to SEM instrument to detect the presence of any viable corrosion byproducts. X-ray diffraction methode was also used to detect any possible emerging corrosion on samples surfaces. The results showed that SS-430 suffers very little corrosion in NaCl environment, and that this material turn out to have an outstanding resistance toward NaCl corrosion. The possible ensuing corrosion byproducts are chrome oxides and iron oxides.